Processing and quality of black pepper - a review - Korikanthimath, P Heartwin Amala Dhas, V S (Journal of Spices and Aromatic Crops, 2003)
Processing of pepper involves different unit operations such as threshing, blanching, drying, cleaning, grading and packaging. these operations are important to ensure clean and quality products. Various mechanical gadgets available for threshing, cleaning, drying, etc. are reviewed. A wide range of threshers with a capacity ranging from 50 to 1200 kg ha-1 are available. However, some of the threshers and cleaners need improvisation for commercial acceptability. Cleanliness and quality standards like Agmark, standards prescribed by American Spice Trade Association (ASTA) and European Spice Association (ESA) are reviewed. Different methods for preparation of value added products like dehydrated green pepper, canned green pepper, white pepper, ground pepper, pepper oil, etc. have also been covered in this review.